(untitled) (Research, Society and Development, 2022)
Benzodiazepines whose pharmacological properties provide sedative, hypnotic, anxiolytic, anticonvulsant and muscle relaxant actions are the most widely used psychotropic drugs with potential to cause chemical dependence. The objective was to analyze the use of benzodiazepines by medical students and their systemic effects and on the levels of attention, anxiety and school performance, since the sedative and hypnotic effects of this drug are potentiated and may reflect in a depressant action on the System. Central Nervous. This is a descriptive-exploratory and cross-sectional research, in which an electronic questionnaire was applied on the use of psychoactive substances, specifically benzodiazepines, in academics enrolled from the 1st to the 9th period of medicine at a medical school in the south of the State of Tocantins, aged over 18 years, both sexes. Of the 126 responses, 64.3% (81) were female and 35.7% (45) were male. It is observed that the most used drug is clonazepam 0.5mg, followed by alprazolam 0.5mg and in amounts equal to alprazolam 1mg and 2mg, clonazepam 2mg and diazepam 5mg and 10mg. The vulnerability of students at the interface to the mental health scenario has increasingly been in line with anxious and depressive profiles, which were evidenced in the present study. The research found that the use of benzodiazepines by medical students is associated with the strenuous routine of studies and the volume of requirements for preparing a doctor, which evolves to the use of medication after entering college.